2011
DOI: 10.1080/09658211.2011.584388
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of ownership and choice on self-memory biases

Abstract: Objects encoded in the context of temporary ownership by self enjoy a memorial advantage over objects owned by other people. This memory effect has been linked to self-referential encoding processes. The current inquiry explored the extent to which the effects of ownership are influenced by the degree of personal choice involved in assigning ownership. In three experiments pairs of participants chose objects to keep for ownership by self, and rejected objects that were given to the other participant to own. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 57 publications
(79 reference statements)
7
42
0
2
Order By: Relevance
“…For example, researchers have reported that subjects had better recall performance for the nouns associating with self-generated names than for nouns linked to names generated by others (47). Others have also shown that, after decision about self-or other-ownership during stimulus encoding, subjects showed better memory for self-related objects compared with those related to other people (26,27). Our results extend the selfassociation benefit to the perceptual domain.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, researchers have reported that subjects had better recall performance for the nouns associating with self-generated names than for nouns linked to names generated by others (47). Others have also shown that, after decision about self-or other-ownership during stimulus encoding, subjects showed better memory for self-related objects compared with those related to other people (26,27). Our results extend the selfassociation benefit to the perceptual domain.…”
Section: Discussionsupporting
confidence: 76%
“…An additional intriguing aspect of "the social self" is the reliance on ownership relations with the environment (25) and the flexibility by which the self "expands" within the environment through acquired associations (26,27). Cunningham et al demonstrated that randomly assigned shopping products as belonging to the self ("mine") versus to another (e.g., "Alex's") increased both the ability of participants to remember and the preferential value of products link with the self (26).…”
mentioning
confidence: 99%
“…Illustrating the relationship between self and agency, Cunningham et al (2011) engaged participants in an ownership task in which they were able to view and choose objects for themselves or others. Personal choice elicited a greater memory bias for self-owned objects than when ownership was assigned by the experimenter.…”
Section: Discussionmentioning
confidence: 99%
“…The memory advantage associated with selfreferencing is known as the 'self-reference effect' (SRE). The SRE can be elicited through surprisingly simple self-item associations, for example by presenting to-beremembered information simultaneously with the participant's own name or face , by assigning items to self through temporary ownership (Cunningham, Turk, MacDonald, & Macrae, 2008) or through self-choice (Cunningham, van den Bos, & Turk, 2011). Several studies have also demonstrated robust SREs in early and middle childhood (Cunningham, Brebner, Quinn, & Turk, 2014;Cunningham Vergunst, Macrae, & Turk, 2013;Ross, Anderson, & Campbell, 2011;Sui & Zhu, 2005).…”
Section: The Self and Memorymentioning
confidence: 99%
“…Specifically, Cunningham, Brady-van den Bos, and Turk (2011) found that items that were identified as belonging to "self" exhibited a memory advantage during recall over those that were identified as belonging to another, even when the sense of ownership was artificial and illusory in nature.…”
Section: Introductionmentioning
confidence: 99%